Implementation and calibration of finite-length plastic hinge elements for use in seismic structural collapse analysis - Ribeiro, Filipe L.A.; Neves, Luis A.C.; Barbosa, Andre R. (Taylor & Francis, 2017)
Finite-length plastic hinge (FLPH) models have shown advantages over the concentrated plasticity hinge (CPH) models. However, empirical phenomenological relationships, such as Modified Ibarra–Medina–Krawinkler (ModIMK) deterioration model, were mainly calibrated for use in CPH models. ModIMK relationships are versatile and have been applied to steel, reinforced concrete, and timber structures. Herein, a calibration procedure of FLPH models and a unified algorithm for use of ModIMK relationships in CPH and FLPH models are presented. Results from included examples validate the proposed algorithms, which were implemented in OpenSees. Additionally, results highlight that FPLH models avoid errors and convergence pitfalls of CPH models.